Regulation of Pseudomonas aeruginosa-Mediated Neutrophil Extracellular Traps - Skopelja-Gardner, Sladjana; Theprungsirikul, Jomkuan; Lewis, Kimberley A.; Hammond, John H.; Carlson, Kyrsten M.; Hazlett, Haley F.; Nymon, Amanda; Nguyen, Dao; Berwin, Brent L.; Hogan, Deborah A.; Rigby, William F. C. (Frontiers in Immunology, 2019)
Pseudomonas aeruginosa is the most prevalent opportunistic pathogen in the airways of cystic fibrosis (CF) patients. The pulmonary disorder is characterized by recurrent microbial infections and an exaggerated host inflammatory immune response led primarily by influx of neutrophils. Under these conditions, chronic colonization with P. aeruginosa is associated with diminished pulmonary function and increased morbidity and mortality. P. aeruginosa has a wide array of genetic mechanisms that facilitate its persistent colonization of the airway despite extensive innate host immune responses. Loss of function mutations in the quorum sensing regulatory gene lasR have been shown to confer survival advantage and a more pathogenic character to P. aeruginosa in CF patients. However, the strategies used by LasR-deficient P. aeruginosa to modulate neutrophil-mediated bactericidal functions are unknown. We sought to understand the role of LasR in P. aeruginosa-mediated neutrophil extracellular trap (NET) formation, an important anti-microbial mechanism deployed by neutrophils, the first-line responder in the infected airway. We observe mechanistic and phenotypic differences between NETs triggered by LasR-sufficient and LasR-deficient P. aeruginosa strains. We uncover that LasR-deficient P. aeruginosa strains fail to induce robust NET formation in both human and murine neutrophils, independently of bacterial motility or LPS expression. LasR does not mediate NET release via downstream quorum sensing signaling pathways but rather via transcriptional regulation of virulence factors, including, but not restricted to, LasB elastase and LasA protease. Finally, our studies uncover the differential requirements for NADPH oxidase in NET formation triggered by different P. aeruginosa strains.